What does not kill you makes you weaker!: Editorial - Maremonti, Francesca; Linkermann, Andreas Günter (Cell death and differentiation, 2026)
Tumor cell evasion from regulated cell death is a hallmark of cancer [1]. Davern et al. now identify resistance to mitochondrial apoptosis to represent the common mechanism by which persister cells that survived either immunotherapy- or irradiation-treatment rely on to proliferate. Therefore, they discovered the persister cells´ Achilles heel for future treatments with BH3-mimetics [2].
Gesehen am 10.02.2026